Bacterial leakage in root canals filled with conventional and MTA-based sealers - Oliveira, A. C. M. [UNESP]; Tanomaru, Juliane Maria Guerreiro [UNESP]; Faria-Junior, N. [UNESP]; Tanomaru-Filho, M. [UNESP] (Wiley-Blackwell, 2011)
P>AimTo evaluate bacterial leakage after filling root canals with several endodontic sealers, including MTA-based materials.MethodologyOne hundred and thirty single-rooted extracted human teeth were randomly divided into experimental groups (n = 15) and two control groups (n = 5). Six root canal sealers were namely: AH Plus (AHP), Sealer 26 (S26), Epiphany SE (ESE), Sealapex (SEL), Active GP (AGP), Endofill (EDF), and two MTA-based sealers were namely: Endo CPM Sealer (CPM) and MTA-based sealer (MTAS, MTA Sealer). Teeth in the control groups were either filled with no sealer or made completely impermeable. Root canals were prepared and filled with either gutta-percha and one of the sealers or with Resilon and Epiphany SE. Teeth were sterilized by ethylene oxide prior to the bacterial leakage experiments using Enterococcus faecalis. Leakage was evaluated every 24 h for 16 weeks. Data were analysed by the Kaplan-Meier, Kruskal-Wallis and Dunn tests at 5% significance.ResultsControl groups had either immediate leakage or no leakage. During 120 days, significantly more leaking samples were detected for AGP, CPM and MTAS (P < 0.05). The best sealing ability was observed for AH Plus and Sealapex (P < 0.05).ConclusionsAll sealers evaluated allowed bacterial leakage. The MTA-based sealers had the most leakage.
Keywords: bacterial leakage; endodontic sealer; MTA; root canal filling material